The performance of concrete using synthetic lightweight coarse aggregate (SYLCAG) on flexural behavior - Siti Nur Amira, Hassan (2015)
Flexural behaviour is one of the element in determine whether the materials involve in the case study can be used as part of the structure. This study reported on the flexural behaviour of reinforced concrete beams construct from synthetic lightweight coarse aggregate (SYLCAG) produced from offshore sand which is used as alternative to replace normal weight aggregate where they are over exploited nowadays. The development of this study were experimentally to determine the capabilities of the offshore sand as synthetic lightweight coarse aggregate (SYLCAG) used in structural reinforced concrete. Compressive strength test were carried out to determine the strength of concrete using SYLCAG. Flexural strength test were carried out with increasing load using four point load test method until the designed reinforced beam fails. The load applied and deflection were recorded in timely manner. Experimental ultimate load capacity and deflection were then compared with the theoretical calculations which calculated from Eurocode 2 for the ultimate load capacity and ACI code or the deflection. The cracks occurred are visualised to determine the mode of failures. This study find that concrete made of SYLCAG has low strength. Other than that, for the four point test, SYLCAG reinforced concrete beam has shown lower load capacity can be taken before the beam fail as about 50% of the normal concrete design of the same strength. At early stage, SYLCAG concrete show positive failure mode and as the load apply increased, it tend to have failure mode in shear.